The dancing master op. 34 : [opera in one act] - Arnold, Malcolm 1921-2006 (Resonus Limited, 2020)
Originally intended as an opera for television, The Dancing Master was considered too racy for viewers in the 1950s and subsequently rejected for broadcast and largely forgotten
Interpreten: Eleanor Dennis (Miranda). Catherine Carby (Prue). Fiona Kimm (Mrs Caution). Ed Lyon (Gerard). Mark Wilde (Monsieur). Graeme Broadbent (Diego). BBC Concert Orchestra. John Andrews (Dirigent)
Aufnahme: Warterford Colosseum, 7.-9. Januar 2020
Keywords: CD